Drug-Free Platelets Can Act as Seeds for Aggregate Formation During Antiplatelet Therapy - Hoefer, Thomas (Arterioscler Thromb Vasc Biol, 2015)
OBJECTIVE—: Reduced antiplatelet drug efficacy occurs in conditions of increased platelet turnover, associated with increased proportions of drug-free, that is, uninhibited, platelets. Here, we detail mechanisms by which drug-free platelets promote platelet aggregation in the face of standard antiplatelet therapy. APPROACH AND RESULTS—: To model standard antiplatelet therapy, platelets were treated in vitro with aspirin, the P2Y(12) receptor blocker prasugrel active metabolite, or aspirin plus prasugrel active metabolite. Different proportions of uninhibited platelets were then introduced. Light transmission aggregometry analysis demonstrated clear positive associations between proportions of drug-free platelets and percentage platelet aggregation in response to a range of platelet agonists. Using differential platelet labeling coupled with advanced flow cytometry and confocal imaging we found aggregates formed in mixtures of aspirin-inhibited platelets together with drug-free platelets were characterized by intermingled platelet populations. This distribution is in accordance with the ability of drug-free platelets to generate thromboxane A(2) and so drive secondary platelet activation. Conversely, aggregates formed in mixtures of prasugrel active metabolite–inhibited or aspirin plus prasugrel active metabolite–inhibited platelets together with drug-free platelets were characterized by distinct cores of drug-free platelets. This distribution is consistent with the ability of drug-free platelets to respond to the secondary activator ADP. CONCLUSIONS—: These experiments are the first to image the interactions of inhibited and uninhibited platelets in the formation of platelet aggregates. They demonstrate that a general population of platelets can contain subpopulations that respond strikingly differently to overall stimulation of the population and so act as the seed for platelet aggregation.